Predominance of dfrG as determinant of trimethoprim resistance in imported Staphylococcus aureus. (December 2015) - Nurjadi, D.; Schäfer, J.; Friedrich-Jänicke, B.; Mueller, A.; Neumayr, A.; Calvo-Cano, A.; Goorhuis, A.; Molhoek, N.; Lagler, H.; Kantele, A.; Van Genderen, P.J.J.; Gascon, J.; et al.
Abstract: To investigate the global occurrence of trimethoprim–sulfamethoxazole resistance and the genetic mechanisms of trimethoprim resistance, we analysed Staphylococcus aureus from travel-associated skin and soft-tissue infections treated at 13 travel clinics in Europe. Thirty-eight per cent (75/196) were trimethoprim-resistant and 21% (41/196) were resistant to trimethoprim–sulfamethoxazole. Among methicillin-resistant S. aureus, these proportions were 30% (7/23) and 17% (4/23), respectively. DfrG explained 92% (69/75) of all trimethoprim resistance in S. aureus . Travel to South Asia was associated with the highest risk of acquiring trimethoprim–sulfamethoxazole-resistant S. aureus . We conclude that globally dfrG is the predominant determinant of trimethoprim resistance in human S. aureus infection.